2021
DOI: 10.1038/s42003-021-02885-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TCR repertoires in functionally competent cytotoxic T cells cross-reactive to SARS-CoV-2

Abstract: SARS-CoV-2-specific CD8+ T cells are scarce but detectable in unexposed healthy donors (UHDs). It remains unclear whether pre-existing human coronavirus (HCoV)-specific CD8+ T cells are converted to functionally competent T cells cross-reactive to SARS-CoV-2. Here, we identified the HLA-A24-high binding, immunodominant epitopes in SARS-CoV-2 spike region that can be recognized by seasonal coronavirus-specific CD8+ T cells from HLA-A24+ UHDs. Cross-reactive CD8+ T cells were clearly reduced in patients with hem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
(90 reference statements)
3
26
0
Order By: Relevance
“…The analysis of the data used to train the predictor of immunogenicity (PRIME) confirmed the importance of aromatic residues, especially tryptophan. In line with previous studies and crystal structures of TCR-peptide-MHC complexes (Calis et al, 2013;Devlin et al, 2020;Schmidt et al, 2021;Shimizu et al, 2021), we suggest that this preference reflects the ability of tryptophan to engage into stable molecular interactions with the TCR. However, we cannot exclude that other factors play a role in the importance given to tryptophan in PRIME.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis of the data used to train the predictor of immunogenicity (PRIME) confirmed the importance of aromatic residues, especially tryptophan. In line with previous studies and crystal structures of TCR-peptide-MHC complexes (Calis et al, 2013;Devlin et al, 2020;Schmidt et al, 2021;Shimizu et al, 2021), we suggest that this preference reflects the ability of tryptophan to engage into stable molecular interactions with the TCR. However, we cannot exclude that other factors play a role in the importance given to tryptophan in PRIME.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, the 9-mer peptide (QYIKWPWYI) fully overlapping with the 10-mer epitope recognized by TCR QYI was shown to elicit an immuno-dominant CD8 + T-cell response and the QYIKWPWYI – HLA-A*24:02 complex was crystallized (Shimizu et al, 2021). This structure shows that the three non-anchor aromatic sidechains shared with the 10-mer investigated in our work (i.e., W5, W7 and Y8) are all facing outside of the HLA-I binding site and therefore are likely to interact with the TCR (Figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies described that pre-existing cross-reactive memory T cells found in some uninfected HCWs (despite being exposed to SARS-CoV-2), as described in pre-pandemic samples, may lead to abortive seronegative infections (Shimizu et al, 2021;Flemming, 2022). This cross-reactivity is likely to be induced by seasonal coronaviruses since they present high sequence conservation.…”
Section: Discussionmentioning
confidence: 96%
“…This difference gives about 12 and 17 times larger in the number of daily cases at a peak and the cumulative number than those in Japan, respectively. The regional k difference would be attributed to the immune response to coronaviruses [9]. Indeed, due to double vaccination, about 20% and 30% increases in the broken-link probability were observed for the 2 nd and 3 rd δ partial waves in Japan, respectively.…”
Section: Discussionmentioning
confidence: 99%